Evaluating unmet needs in patients undergoing surgery for colorectal cancer: a patient reported outcome measures study. (23rd March 2019) - Sutton, P. A.; Bourdon‐Pierre, R.; Smith, C.; Appleton, N.; Lightfoot, T.; Gabriel, C.; Richards, B.; Mohamed, S.; Mason‐Whitehead, E.; Hulbert‐Williams, N. J.; Vimalachandran, D.
Abstract: Aim: Patient reported outcome measures (PROMs) are self‐reported measures of patients' health status or health‐related quality of life at a single point in time. We aimed to evaluate the use of a colorectal PROM and conducted a focus group to further explore this and other unmet needs in our patient population treated surgically for colorectal cancer. Method: A multidisciplinary research group consisting of colorectal surgeons, nurse specialists, psychologists, sociologists and patient representatives devised a composite tool of new and existing outcome measures which was piloted in our local population ( n  = 35). Participants were subsequently invited to attend a semi‐structured focus group during which the PROM was reviewed and an unmet needs analysis was performed. Thematic analysis of focus group transcripts was undertaken for emergent themes. Results: Initial consensus was for a tool including the EQ‐5D, Functional Assessment of Cancer Therapy – Colorectal (FACT‐C), the distress thermometer, a validated measure of stigma, an unmet needs analysis, and questions assessing the psychological impact of cancer. Median and interquartile range values suggested that all metrics were discriminatory with the exception of FACT‐C. All participants agreed that the tool was acceptable and reflected the current state of their health and emotions. Thematic analysis of focus group transcripts identified four major themes: physical symptoms, emotional response, information provision and coping mechanisms. Conclusion: Through expert consensus, local piloting and patient focus groups we have evaluated a novel PROM for colorectal cancer. Furthermore, through our direct engagement with patients we have identified several unmet needs which we are currently exploring within the clinical service.